Impact of Educational Program Regarding First-aid Knowledge among the Teenagers - Renuka, K.; Kamala, S. (International Journal of Nursing Research, 2023)
Introduction: The teachers and teenagers spend considerable hours together within the school environment. Schools are common places where they can find a noticeable risk of physical injuries. The aim of the study: The aim of the study was to evaluate the impact of an educational program regarding first-aid knowledge among teenagers. Methods: Quasi-experimental study with one group pre-/post-test research design was used. The multistage random sample used to select the five groups and the participated 50 teenagers. A structured self-administered questionnaire such as, demographic data and assessment of first aid knowledge questionnaire was used for data collection (Pre-test and Posttest). The findings of the study revealed that mean ± SD of teenagers age were 36.78 ± 7.83, 99% of the teenagers attended an educational program about first aid, there were statistical significant differences between total score of teenagers knowledge (P = 0.001) in pre- and post-test. There was a statistically significant difference between the performance level of teenagers (P = 0.001*). Conclusion: The study showed that there was an improvement of teenager’s knowledge and practices regarding first aid after the educational program. The study recommended that continuous educational and training programs for teenagers and public as a whole about first aid.